Research on the Main Challenges and Countermeasures in Sci-Tech Finance - Liu Yunze (SHS Web of Conferences, 2025)
Fuelled by advancements in science and technology, traditional finance struggles to fulfil current demands, highlighting the need for optimization in technological finance to promote high-quality development. This paper mainly discusses the development status, major problems and countermeasures of science and technology financing in China. This document highlights that companies involved in science and technology face significant financing demands and substantial risks, whereas the backing from conventional financial systems is inadequate. Additionally, it notes issues such as the misalignment between the financial framework and innovation, a tendency for short-term investments, and a weak connection between investment and credit. In light of these challenges, this paper suggests measures such as refining the multi-tier capital market, enhancing the bank credit system, increasing the availability of long-term funding, improving the legal and regulatory framework, and optimizing the connection between investment and credit. These steps aim to strengthen the financing capacity of science and technology firms, facilitate the industrial application of technological innovations, and promote the close integration of technology and finance.